A recombinant glutamine-binding protein from Escherichia coli: effect of ligand-binding on protein conformational dynamics - Herman, Petr; Vecer, Jaroslav; Scognamiglio, Viviana; Staiano, Maria; Rossi, Mose'; D'Auria, Sabato (Biotechnology progress, 2004)
We have investigated the effect of the binding of glutamine on the conformational dynamics of the recombinant glutamine binding protein (GlnBP) from Escherichia coli by steady-state and time-resolved fluorescence techniques. The structural stability of the protein was also studied by far-UV circular dichroism spectroscopy in the range of temperature between 25 and 80 degrees C. The results showed that the interaction of the protein with the ligand resulted in a marked change of the structural and conformational dynamics features of the protein. In particular, the fluorescence and circular dichroism data showed that the presence of glutamine resulted in a dramatic increase of the protein thermal stability of about 10 degrees C. In addition, the fluorescence time-resolved data pointed out that both in the absence and in the presence of glutamine the protein structure was highly rigid with small amplitude of segmental motion up to 65 degrees C and a low accessibility of the protein tryptophan residues to acrylamide. The obtained results on the structural properties of the recombinant glutamine-binding protein in the absence and in the presence of glutamine can contribute to a better understanding of the transport-related functions of the protein and structurally similar periplasmic transport proteins, as well as to the design and development of new biotechnological applications of this class of proteins.
Keywords: kinetika; ligandy; Protein Binding; Carrier Proteins; rekombinantní proteiny; Glutamine; Recombinant Proteins; Ligands; Protein Conformation; Escherichia coli; vztahy mezi strukturou a aktivitou; Temperature; Binding Sites; vazba proteinů; Kinetics; glutamin; Structure-Activity Relationship; transportní proteiny; vazebná místa; teplota; konformace proteinů